How is Gender Described in Academic Writing and News Article : A Corpus-Based Study - Esty Yuliana Puspasari; Elvi Citraresmana; Tubagus Chaeru Nugraha (Universitas Cokroaminoto Palopo, 2022)
Gender is cannot be separated in English grammar. This influence is variable and gender has several categories that have emerged in recent years. This study aims to recognize gender through close collocations with the word. To support this research is to conduct a corpus research method through the Antconc application. the word gender is searched through the frequency that occurs the most and what nouns are related to gender. The data sources of this study were ten articles each from Gender& Society, SAGE Journal, and news articles from the Associated Press related to the topic of gender identity. The conclusion obtained is that the mental state in the word gender is very influential so it requires a neutral pronoun to talk about this.